Optimizing Emergency Department Patient Flow Through Bed Allocation Strategies: A Discrete-Event Simulation Study - Sen-Tian Wang MD; Shao-Jen Weng PhD; Ting-Yu Yeh MS; Chih-Hao Chen MS; Yao-Te Tsai PhD (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Emergency department (ED) overcrowding and prolonged length of stay (LOS) remain critical issues in healthcare systems. This study compared 4 bed allocation strategies to optimize patient flow and resource utilization in a regional teaching hospital in Taiwan. A discrete-event simulation model was developed using 1 year hospital data from January 2022, including 29 718 ED visits. The following strategies were evaluated: (1) intra-departmental bed sharing, (2) optimized bed allocation, (3) cross-departmental bed lending with 5% capacity, and (4) combined optimization with bed borrowing. The model was validated by t -tests comparing the simulation outputs with actual hospital data. Results: All strategies demonstrated improvement compared to current operations. Of these, Strategy 4, combined optimization with bed borrowing, was the most promising: it maintained stable ED nursing utilization at 45.65% with a 95% confidence interval (CI) of 45.60% to 45.71% while reducing the cases of extended LOS. The rates of ED LOS exceeding 6, 12, and 24 h were 2.48%, 0.38%, and 0.12%, respectively, which is a significant improvement compared with the baseline. Optimization alone contributed to a 20% improvement in extended LOS under Strategy 2, while additional bed-sharing policies further improved performance by 10%. Conclusions: Strategic bed allocation combined with controlled bed-sharing policies achieved a 30% reduction in extended ED LOS without increasing nursing workload. The optimal strategy (Strategy 4) reduced cases of ED LOS exceeding 6 h to 2.48% while maintaining stable nursing utilization at 45.65%, demonstrating the effectiveness of combining optimization with resource sharing in ED patient flow management.